Determinasi Kinerja Keuangan: Leverage, Ukuran Perusahaan, Financial Distress, Dan Intensitas Modal Pada Perusahaan Sektor Pertambangan - Natrion Natrion; Christina Christina (Pasca Sarjana Universitas Satya Negara Indonesia, 2026)
This study was conducted to examine the effect of leverage, firm size, financial distress, and capital intensity on the financial performance of mining sector companies listed on the Indonesia Stock Exchange (BEI) during the 2020–2024 period, with financial performance measured using Return on Assets (ROA). The study is causal in nature and utilizes secondary data obtained from annual financial statements. The population includes all mining companies listed on the BEI during the study period, while the sample was selected using purposive sampling, resulting in 14 companies that met the criteria and a total of 70 observations. Data analysis was performed using multiple linear regression with the assistance of SPSS version 20. Partial test results indicate that firm size and capital intensity have an effect on financial performance, whereas financial distress does not have a significant impact. Simultaneous testing confirms that all four variables collectively contribute to the financial performance of the mining companies included in the study